A. Ben Shemesh's Introductions in Taxation in Islam: Comments on His Sources and Interpretation - Suharto, Ugi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A. Ben Shemesh's Introductions in Taxation in Islam: Comments on His Sources and Interpretation